Rethinking gender, crime, and justice : feminist readings - Renzetti, Claire M.; Goodstein, Lynne; Miller, Susan L. (Roxbury, 2006)
This collection is designed to deepen students' understanding about the essential role that gender plays in the commission of - and societal responses to - criminal behavior. "Rethinking Gender, Crime, and Justice" demonstrates how our notions of gender, race, and class influence both how society defines crime as well as how offenders commit crimes and are "treated" for their actions. The book includes a rich variety of national and global perspectives. It reviews the most up-to-date knowledge on gender and crime, women as offenders and victims, and the impact of gender on policing, corrections administration, and the courts. The essays in this collection are engagingly and accessibly written. They challenge students to question their assumptions about criminality, victimization, and how such situations are - and should be - approached. "Rethinking Gender, Crime, and Justice" covers issues that are frequently left out of traditional criminology texts.